Spinel oxide as well as synthesis method and application thereof

By using anhydrous metal nitrate salts and hydrated metal nitrate salts in spinel oxide synthesis and using molten salt media, the precise regulation of cation sites is achieved, the problem of insufficient chemical uniformity and phase purity of materials is solved, and the stability and service life of lithium-sulfur batteries are significantly improved.

CN119551737APending Publication Date: 2025-03-04GUANGDONG UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411441783.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

It is difficult for existing spinel oxide materials to accurately regulate the distribution of cation sites during the synthesis process, resulting in insufficient chemical uniformity and phase purity of the material, affecting its electrochemical performance.

Method used

The anhydrous metal nitrate salt and hydrated metal nitrate salt are synthesized with molten salt as reaction medium, and the uniformity of cation distribution is ensured by precisely regulating the cationic site occupation in the spinel structure.

Benefits of technology

The chemical uniformity and phase purity of spinel oxide materials are improved, making their structure more stable and their chemical compositions uniform, thereby significantly improving its stability and service life in lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551737A_ABST
    Figure CN119551737A_ABST
Patent Text Reader

Abstract

The invention relates to a spinel oxide as well as a synthesis method and application thereof. The spinel oxide is synthesized from anhydrous nitric acid metal salt and hydrated nitric acid metal salt by taking fused salt as a reaction medium; the structural type of the material is AB2O4 type, and the microstructure of the material is a layered structure or a flower-like structure formed by stacking nanosheets; the synthesis method of the spinel oxide comprises the following steps: mixing anhydrous nitric acid metal salt and hydrated nitric acid metal salt according to a molar ratio of 1: (1-3) to obtain a mixed precursor material; a fused salt medium and the mixed precursor material are selected to be mixed according to the molar ratio of 1: (1-5), heating is conducted, and oxide of a spinel structure is obtained; the chemical uniformity and phase purity of the material are improved by accurately regulating and controlling the occupation condition of cation sites in the spinel structure, so that the structure is more stable, the chemical components are uniform, and excellent stability and reliability are shown in the subsequent application of the lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical materials and electrochemistry, and in particular relates to a spinel oxide and a synthesis method and application thereof. Background Art

[0002] Lithium-sulfur batteries have a high theoretical energy density (2600Wh kg -1 ), is widely considered to be one of the important candidates for the next generation of energy storage devices. However, the widespread commercialization of lithium-sulfur batteries faces many technical challenges, including polysulfide shuttle effect, lithium dendrite growth and electrochemical instability of diaphragm materials. In order to improve the cycle performance and electrochemical stability of lithium-sulfur batteries, the development of new diaphragm materials with excellent ionic conductivity, chemical stability and polysulfide adsorption capacity has become a research hotspot.

[0003] Among many diaphragm materials, spinel structure oxides are considered to be ideal candidates for diaphragm materials due to their unique structural advantages. 2 O 4 ) The cations at the A position occupy the tetrahedral sites and the cations at the B position occupy the octahedral sites. The performance of the material depends largely on the distribution of the cations in these sites. Precisely controlling the cation occupancy at these sites can directly affect the physical and chemical properties of the material, such as conductivity, ion diffusion rate, chemical stability, etc., thereby optimizing its performance in battery separators.

[0004] However, in the synthesis of spinel oxide materials, the existing technology still faces great challenges in site regulation, mainly including the following aspects: 1. The difficulty of site regulation. In the spinel structure, the distribution of cations at tetrahedral and octahedral sites directly determines the electron and ion transport capacity of the material, which in turn affects its performance in electrochemical devices. Generally, there are significant differences in the size, electronic structure and chemical valence of cations at the A and B sites. Therefore, how to effectively regulate the distribution of ions at these sites to achieve the purpose of optimizing material performance is a core issue in the prior art. Traditional synthesis methods such as solid-state reaction method, sol-gel method and hydrothermal method often have limitations in site regulation. These methods rely on solid-state diffusion or liquid phase reaction, and it is difficult to ensure the precise distribution of ions at the A and B sites during the reaction process. During the reaction process, due to the limitations of thermodynamics and diffusion rate, the arrangement of ions in the crystal is often uneven, resulting in poor chemical uniformity of the material. This uneven cation distribution not only affects the structural stability of the material, but may also cause local defects and reduce the phase purity and electrochemical activity of the material. 2. Defects and impurities in the crystal structure. In the synthesis of spinel oxide materials, if the cation distribution at the site cannot be precisely controlled, it is easy to cause the material to generate an amorphous phase, a heterogeneous phase or crystal defects. These defects not only weaken the conductivity and ion diffusion capacity of the material, but also lead to a decrease in the electrochemical performance of the material, especially in high-rate discharge and long-cycle applications. Defects in the crystal structure often come from the inability of cations to be evenly distributed at the specified site.

[0005] In order to overcome the above problems, existing studies have attempted to improve the performance of spinel oxides by ion doping, surface coating or the use of additives. Although these methods have improved the chemical stability and electrochemical properties of the materials to a certain extent, there are still deficiencies in site regulation. The ion doping strategy usually introduces metal cations of different valence states, such as Al, Mg, etc., into the spinel structure to adjust the ion occupancy of the A and B sites. However, this method is difficult to achieve precise control of the sites, the distribution of doped ions at different sites still has great uncertainty, and defects may still exist in the doped material. Summary of the invention

[0006] Based on this, the purpose of the present invention is to provide a spinel oxide and its synthesis method and application, and to obtain a spinel oxide material with high chemical uniformity and phase purity through precise regulation of the cationic sites in the spinel structure, thereby improving its electrochemical properties, especially improving its stability and service life in lithium-sulfur batteries.

[0007] To achieve the above object, the present invention provides the following solutions:

[0008] A spinel oxide synthesized from anhydrous metal nitrate and hydrated metal nitrate using molten salt as a reaction medium; its structural type is AB 2 O 4 The microstructure of the nanostructured nanoparticles is a layered structure or a flower-like structure formed by the accumulation of nanosheets.

[0009] The present invention relates to a spinel oxide, which improves the chemical uniformity and phase purity of the material by precisely regulating the occupancy of cationic sites in the spinel structure, so that the structure of the spinel oxide material is more stable and the chemical composition is uniform, thereby showing excellent stability and reliability in subsequent applications of lithium-sulfur batteries, and solving the problem of site regulation in the preparation process of existing spinel oxide materials.

[0010] Furthermore, A and B can be mono-elements or poly-elements, A is one or more of Ni, Co, Fe, Mn, Cu, Zn, and Mg, and B is one or more of Co, Fe, Al, and Cr.

[0011] A method for synthesizing spinel oxide, comprising the following steps:

[0012] Mixing anhydrous metal nitrate and hydrated metal nitrate in a corresponding ratio of 1 to obtain a mixed precursor material;

[0013] Selecting a molten salt medium and the mixed precursor material in a corresponding ratio of 2, and heating them to obtain a spinel structure oxide;

[0014] Wherein, the molar ratio of the corresponding ratio 1 is 1:1-3; the molar ratio of the corresponding ratio 2 is 1:1-5.

[0015] A method for synthesizing a spinel oxide of the present invention adopts molten salt as a reaction medium. The high ion mobility and reactivity in a molten salt environment make site regulation more efficient, thereby promoting ion replacement and atomic diffusion, ensuring that cations in the spinel structure can accurately occupy target sites, and realizing precise regulation of cations in tetrahedral and octahedral positions in the spinel structure through a reasonable ratio of anhydrous metal nitrate salts and hydrated metal nitrate salts, thereby ensuring the uniformity of cation distribution in the material and avoiding the problem of chemical inhomogeneity caused by uneven positions of cations, so that it has a wide range of applications in multiple fields, and is particularly suitable for use as diaphragm materials, catalyst carriers and energy storage materials in electrochemical devices; the material performance is improved through precise site regulation, overcoming the limitations of site regulation in traditional processes. In addition, a method for synthesizing spinel oxides of the present invention can achieve efficient material synthesis at a relatively low temperature, thereby reducing reaction time and energy consumption and lowering production costs. Compared with traditional spinel oxide synthesis methods, the present invention has the significant advantages of simplified process, short reaction time and low energy consumption. By optimizing the reaction conditions, not only the performance of the material is improved, but also the complex subsequent processing steps are greatly reduced, so that the synthesis process has a strong potential for industrial production, which is helpful to promote the large-scale continuous production and application of spinel oxides in the fields of energy storage and catalysis.

[0016] Furthermore, the anhydrous nitrate metal salt is a mixture of one or more of the following: anhydrous nickel nitrate (Ni(NO 3 ) 2 ), anhydrous ferrous nitrate (Fe(NO 3 ) 2 ), anhydrous ferric nitrate (Fe(NO 3 ) 3 ), anhydrous cobalt nitrate (Co(NO 3 ) 2 )、Anhydrous manganese nitrate (Mn(NO 3 ) 2 ), anhydrous copper nitrate (Cu(NO 3 ) 2 )、Anhydrous zinc nitrate (Zn(NO 3 ) 2 )、Anhydrous magnesium nitrate (Mg(NO 3 ) 2 ).

[0017] Furthermore, the hydrated metal nitrate salt is a mixture of one or more of the following: cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O), ferric nitrate nonahydrate (Fe(NO 3 ) 3 9H 2 O), chromium nitrate nonahydrate (Cr(NO3 ) 3 9H 2 O), aluminum nitrate nonahydrate (Al(NO 3 ) 3 9H 2 O) a mixture of multiple types.

[0018] Furthermore, the molten salt medium is a mixture of one or more of the following: potassium chloride (KCl), sodium chloride (NaCl), sodium nitrate (NaNO 3 ), potassium nitrate (KNO 3 ), calcium chloride (CaCl 2 ), magnesium chloride (MgCl 2 )Sodium carbonate (Na 2 CO 3 ), sodium sulfate (Na 2 SO 4 ). The synthesis method of spinel oxide of the present invention adopts the molten salt method. The molten salt used in the molten salt method can be removed by simple washing after the reaction, and is easy to separate and reuse. It is not only economical and sustainable, but also avoids the environmental pollution risk caused by the use of harmful chemical reagents. It is environmentally friendly and meets the requirements of sustainable development of the modern chemical industry. It reduces the burden on the environment, making the preparation method more socially valuable.

[0019] Furthermore, the mixing method is a planetary ball mill, the main disc speed is 50-450r / min, the grinding jar speed is 100-900r / min, the ball milling is 0-2h; the heating temperature is 300-800°C, and the time is 1-12h.

[0020] A modified separator for a lithium-sulfur battery comprises the spinel oxide.

[0021] The spinel oxide material of the present invention, whose sites can be precisely controlled, exhibits excellent electrochemical stability in the application of lithium-sulfur battery separators. By optimizing the structural design of the material, it can maintain a good crystal structure and morphology during the charge and discharge process, and improves its stability under high current density, especially showing significant advantages in electrochemical stability, ionic conductivity and polysulfide adsorption capacity, significantly improving its performance in lithium-sulfur battery separators, solving the problem that traditional separator materials are prone to structural collapse or degradation after multiple charge and discharge cycles, and significantly extending the cycle life of the battery, so that the material of the present invention has broader application prospects in the field of lithium-sulfur batteries.

[0022] A method for preparing the modified lithium-sulfur battery diaphragm comprises the following steps:

[0023] The spinel oxide is mixed evenly with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP), and the mixture is coated on a diaphragm, and the N-methylpyrrolidone (NMP) is volatilized to obtain the modified diaphragm for a lithium-sulfur battery.

[0024] A lithium-sulfur battery comprises the lithium-sulfur battery modified diaphragm.

[0025] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 is a schematic diagram of the structural formula of the spinel oxide according to the present invention;

[0028] Figure 2 The spinel oxide NiCo prepared in Example 1 with precise site control 2 O 4 XRD pattern of

[0029] Figure 3 The spinel oxide NiCo prepared in Example 1 with precise site control 2 O 4 TEM images of

[0030] Figure 4 The spinel oxide NiCo prepared in Example 1 with precise site control 2 O 4 SEM images of

[0031] Figure 5 The site-precisely controlled spinel oxide FeCo prepared in Example 2 2 O 4 XRD pattern of

[0032] Figure 6 The site-precisely controlled spinel oxide FeCo prepared in Example 2 2 O 4 TEM images of

[0033] Figure 7 The site-precisely controlled spinel oxide FeCo prepared in Example 2 2 O 4 SEM images of

[0034] Figure 8 The spinel oxide Co prepared in Example 3 with precise site control 3 O 4 XRD pattern of

[0035] Fig. 9 The spinel oxide Ni prepared in Example 4 with precise site control 0.5 Fe 0.5 Co 2 O 4 XRD pattern of

[0036] Fig.10 This is a cycle performance diagram of the spinel oxide with precise site control prepared in Example 1, Example 2 and Example 3 for lithium-sulfur battery modified diaphragm. DETAILED DESCRIPTION

[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0038] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0042] A spinel oxide, synthesized from anhydrous metal nitrate and hydrated metal nitrate using molten salt as a reaction medium; its structural formula is as follows Figure 1 AB shown 2 O 4 type, whose microstructure is a layered structure or a flower-like structure formed by the accumulation of nanosheets; wherein A and B in the chemical formula are completely replaced by one or more elements on the basis of keeping the total number of atoms unchanged, so A and B can be mono-element or poly-element, A can be one or more of Ni, Co, Fe, Mn, Cu, Zn, Mg, etc., and B can be one or more of Co, Fe, Al, Cr, etc.

[0043] A method for synthesizing spinel oxide, comprising the following steps:

[0044] Mixing anhydrous metal nitrate and hydrated metal nitrate in a molar ratio of 1:1 to 3 to obtain a mixed precursor material;

[0045] A molten salt medium is selected and mixed with the mixed precursor material in a corresponding ratio of 1:1 to 5 in a molar ratio, and the mixture is placed in a heating device for heating for 1 to 12 hours at a heating temperature of 300 to 800° C. to obtain a spinel structure oxide.

[0046] Furthermore, the mixing method is a planetary ball mill, the main disc speed is 50-450r / min, the grinding jar speed is 100-900r / min, and the ball milling time is 0-2h.

[0047] Furthermore, the anhydrous nitrate metal salt is a mixture of one or more of the following: anhydrous nickel nitrate (Ni(NO 3 ) 2 ), anhydrous ferrous nitrate (Fe(NO 3 ) 2 ), anhydrous ferric nitrate (Fe(NO 3 ) 3 )Anhydrous cobalt nitrate (Co(NO 3 ) 2 )、Anhydrous manganese nitrate (Mn(NO 3 ) 2 ), anhydrous copper nitrate (Cu(NO 3 ) 2 )、Anhydrous zinc nitrate (Zn(NO 3 ) 2 )、Anhydrous magnesium nitrate (Mg(NO 3 ) 2 ).

[0048] Furthermore, the hydrated metal nitrate is a mixture of the following: cobalt nitrate hexahydrate (Co(NO3 ) 2 6H 2 O), ferric nitrate nonahydrate (Fe(NO 3 ) 3 9H 2 O), chromium nitrate nonahydrate (Cr(NO 3 ) 3 9H 2 O), aluminum nitrate nonahydrate (Al(NO 3 ) 3 9H 2 O) a mixture of multiple types.

[0049] Furthermore, the molten salt medium is a mixture of one or more of the following: potassium chloride (KCl), sodium chloride (NaCl), sodium nitrate (NaNO 3 ), potassium nitrate (KNO 3 ), calcium chloride (CaCl 2 ), magnesium chloride (MgCl 2 )Sodium carbonate (Na 2 CO 3 ), sodium sulfate (Na 2 SO 4 ).

[0050] A modified separator for a lithium-sulfur battery comprises the spinel oxide.

[0051] A method for preparing the modified lithium-sulfur battery diaphragm comprises the following steps: uniformly mixing the spinel oxide with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP), applying the mixture on the diaphragm, and volatilizing the N-methylpyrrolidone (NMP) to obtain the modified lithium-sulfur battery diaphragm.

[0052] A lithium-sulfur battery comprises the lithium-sulfur battery modified diaphragm.

[0053] Example 1

[0054] A spinel oxide NiCo in this embodiment 2 O 4 The synthesis method comprises the following steps:

[0055] (1) Weigh 1.827 g (10 mmol) of anhydrous nickel nitrate and 5.8207 g (20 mmol) of cobalt nitrate hexahydrate respectively and add them into a planetary ball mill. The main disc speed is 60 r / min and the ball milling is carried out for 30 min.

[0056] (2) Weigh 2.6325 g (45 mmol) of sodium chloride and 3.35475 g (45 mmol) of potassium chloride respectively and add them to the planetary ball mill described in step (1). The main disk speed is 60 r / min and the ball milling is carried out for 60 min.

[0057] (3) Based on step (2), take out the ball-milled material and put it into a 50 mL quartz crucible.

[0058] (4) Based on step (3), the crucible is placed in a muffle furnace, kept at 350° C. for 2 h, naturally cooled, rinsed with deionized water and ethanol, and dried to obtain spinel oxide NiCo 2 O 4 .

[0059] The spinel oxide NiCo prepared in this example 2 O 4 The X-ray diffractometer (XRD) diagram is as follows Figure 2 As shown in the transmission electron microscope (TEM) Figure 3 As shown in the scanning electron microscope (SEM) Figure 4 As shown. Figure 3 , Figure 4 It can be seen that the spinel oxide NiCo 2 O 4 The morphology is layered. Figure 2 The diffraction peaks in the XRD spectrum of the prepared NiCo are consistent with the standard card (JCPDSPDF#97-002-4211), indicating that the prepared sample is pure phase NiCo 2 O 4 , no other impurity phases appear, proving that the material has a high phase purity.

[0060] A method for preparing a modified lithium-sulfur battery diaphragm of this embodiment comprises the following steps:

[0061] The spinel oxide NiCo 2 O 4 The mixture is uniformly mixed with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and coated on a polypropylene microporous membrane Celgard2400 separator, and the N-methylpyrrolidone (NMP) is volatilized to obtain a lithium-sulfur battery modified separator.

[0062] The method for preparing a lithium-sulfur battery using the modified lithium-sulfur battery diaphragm of this embodiment comprises the following steps:

[0063] According to the mass ratio of 7:2:1, the carbon nanotubes (CNT / S) after molten sulfur, the superconducting carbon black (SuperP) conductive agent and the polyvinylidene fluoride (PVDF) binder are weighed and mixed, and then N-methylpyrrolidone (NMP) with a mass of 19 times that of PVDF is added, and the mixture is fully stirred into a paste, and then coated on the current collector aluminum foil with a scraper, and then placed in a vacuum drying oven at 60°C for 8 hours, and cut to prepare a pole piece (φ=14mm), and a pole piece with an active material load of 1mg is obtained as a positive electrode of a lithium-sulfur battery. Then the lithium-sulfur battery positive electrode and the lithium-sulfur battery modified diaphragm are transferred to a glove box filled with argon gas for assembly of a button battery; the button battery model is CR2032, the positive electrode is CNT / S, and the electrolyte is 1.0MLiTFSI (bistrifluoromethanesulfonic acid imide lithium) + 2.0wt% LiNO3 (lithium nitrate) dissolved in 1:1DOL (1,3-dioxolane): DME (ethylene glycol dimethyl ether).

[0064] Example 2

[0065] A spinel oxide FeCo in this embodiment 2 O 4 The synthesis method comprises the following steps:

[0066] (1) Weigh 1.79859 g (10 mmol) of anhydrous ferrous nitrate and 5.8207 g (20 mmol) of cobalt nitrate hexahydrate into a planetary ball mill. The main disc speed is 60 r / min and the ball milling is carried out for 30 min.

[0067] (2) Weigh 2.6325 g (45 mmol) of sodium chloride and 3.35475 g (45 mmol) of potassium chloride respectively and add them to the planetary ball mill described in step (1). The main disk speed is 60 r / min and the ball mill is performed for 30 min.

[0068] (3) Based on step (2), take out the ball-milled material and put it into a 50 mL quartz crucible.

[0069] (4) Based on step (3), the crucible is placed in a muffle furnace, kept at 350° C. for 2 h, naturally cooled, rinsed with deionized water and ethanol, and dried to obtain spinel oxide FeCo 2 O 4 .

[0070] The spinel oxide FeCo prepared in this example 2 O 4 The X-ray diffractometer (XRD) diagram is as follows Figure 5 As shown in the transmission electron microscope (TEM) Figure 6 As shown in the scanning electron microscope (SEM) Figure 7 As shown. Figure 6, Figure 7 It can be seen that the spinel oxide FeCo 2 O 4 The morphology is a nanostructured structure formed by the accumulation of rice layers. Figure 2 The diffraction peaks in the XRD spectrum of the prepared sample are consistent with the standard card (JCPDSPDF#96-153-3163), indicating that the prepared sample is pure FeCo 2 O 4 , no other impurity phases appear, proving that the material has a high phase purity.

[0071] A method for preparing a modified lithium-sulfur battery diaphragm of this embodiment comprises the following steps:

[0072] The spinel oxide FeCo 2 O 4 The mixture is uniformly mixed with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and coated on a polypropylene microporous membrane Celgard2400 separator, and the N-methylpyrrolidone (NMP) is volatilized to obtain a lithium-sulfur battery modified separator.

[0073] The method for preparing a lithium-sulfur battery using the modified lithium-sulfur battery diaphragm in this embodiment is the same as that in Example 1.

[0074] Example 3

[0075] A spinel oxide Co in this embodiment 3 O 4 The synthesis method comprises the following steps:

[0076] (1) Weigh 1.82943 g (10 mmol) of anhydrous cobalt nitrate and 5.8207 g (20 mmol) of cobalt nitrate hexahydrate into a planetary ball mill. The main disc speed is 120 r / min and the ball milling is carried out for 60 min.

[0077] (2) Weigh 4.5495 g (45 mmol) of potassium nitrate and 3.82455 g (45 mmol) of sodium nitrate respectively and add them to the planetary ball mill described in step (1). The main disk speed is 120 r / min and the ball milling is carried out for 60 min.

[0078] (3) Based on step (2), take out the ball-milled material and put it into a 50 mL quartz crucible.

[0079] (4) Based on step (3), the crucible is placed in a muffle furnace, kept at 350° C. for 2 h, naturally cooled, rinsed with deionized water and ethanol, and dried to obtain spinel oxide Co 3 O 4 .

[0080] The spinel oxide Co prepared in this example 3 O 4 The X-ray diffractometer (XRD) diagram is as follows Figure 8 shown. Figure 8 The diffraction peaks in the XRD spectrum are consistent with the standard card (JCPDSPDF#00-009-0418), indicating that the prepared sample is pure phase Co 3 O 4 , no other impurity phases appear, proving that the material has a high phase purity.

[0081] A method for preparing a modified lithium-sulfur battery diaphragm of this embodiment comprises the following steps:

[0082] The spinel oxide Co 3 O 4 The mixture is uniformly mixed with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and coated on a polypropylene microporous membrane Celgard2400 separator, and the N-methylpyrrolidone (NMP) is volatilized to obtain a lithium-sulfur battery modified separator.

[0083] The method for preparing a lithium-sulfur battery using the modified lithium-sulfur battery diaphragm in this embodiment is the same as that in Example 1.

[0084] Example 4

[0085] A spinel oxide N of this embodiment i0.5 Fe 0.5 Co 2 O 4 The synthesis method comprises the following steps:

[0086] (1) Weigh 0.800295 g (5 mmol) of anhydrous ferric nitrate, 0.9135 g (5 mmol) of anhydrous nickel nitrate, and 5.8207 g (20 mmol) of cobalt nitrate hexahydrate into a planetary ball mill. The main disc speed is 120 r / min and the ball mill is performed for 30 min.

[0087] (2) Weigh 1.265 g (90 mmol) of sodium chloride and add it to the planetary ball mill described in step (1). The main disc speed is 120 r / min and the ball mill is performed for 30 min.

[0088] (3) Based on step (2), take out the ball-milled material and put it into a 50 mL quartz crucible.

[0089] (4) Based on step (3), the crucible is placed in a muffle furnace, kept at 350° C. for 2 h, naturally cooled, rinsed with deionized water and ethanol, and dried to obtain spinel oxide N i0.5Fe 0.5 Co 2 O 4 .

[0090] The spinel oxide N prepared in this example i0.5 Fe 0.5 Co 2 O 4 The X-ray diffractometer (XRD) diagram is as follows Fig. 9 shown. Fig. 9 The diffraction peaks in the XRD spectrum are between NiCo 2 O 4 Standard card (JCPDSPDF#97-002-4211) and FeCo 2 O 4 The standard card (JCPDSPDF#96-153-3163) shows that the prepared sample is pure phase N i0.5 Fe 0.5 Co 2 O 4 , no other impurity phases appear, proving that the material has a high phase purity.

[0091] A method for preparing a modified lithium-sulfur battery diaphragm of this embodiment comprises the following steps:

[0092] The spinel oxide N i0.5 Fe 0.5 Co 2 O 4 The mixture is uniformly mixed with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and coated on a polypropylene microporous membrane Celgard2400 separator, and the N-methylpyrrolidone (NMP) is volatilized to obtain a lithium-sulfur battery modified separator.

[0093] The method for preparing a lithium-sulfur battery using the modified lithium-sulfur battery diaphragm in this embodiment is the same as that in Example 1.

[0094] Example 5

[0095] A spinel oxide N of this embodiment i0.1 Fe 0.9 Co 2 O 4 The synthesis method comprises the following steps:

[0096] (1) Weigh 1.440531 g (9 mmol) of anhydrous ferric nitrate, 0.1827 g (1 mmol) of anhydrous nickel nitrate, and 5.8207 g (20 mmol) of cobalt nitrate hexahydrate into a planetary ball mill. The main disc speed is 120 r / min and the ball milling is performed for 60 min.

[0097] (2) Weigh 2.6325 g (45 mmol) of sodium chloride and 3.35475 g (45 mmol) of potassium chloride respectively and add them to the planetary ball mill described in step (1). The main disk speed is 120 r / min and the ball milling is carried out for 60 min.

[0098] (3) Based on step (2), take out the ball-milled material and put it into a 50 mL quartz crucible.

[0099] (4) Based on step (3), the crucible is placed in a muffle furnace, kept at 450° C. for 2 h, naturally cooled, rinsed with deionized water and ethanol, and dried to obtain spinel oxide N i0.1 Fe 0.9 Co 2 O 4 .

[0100] A method for preparing a modified lithium-sulfur battery diaphragm of this embodiment comprises the following steps:

[0101] The spinel oxide N i0.1 Fe 0.9 Co 2 O 4 The mixture is uniformly mixed with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and coated on a polypropylene microporous membrane Celgard2400 separator, and the N-methylpyrrolidone (NMP) is volatilized to obtain a lithium-sulfur battery modified separator.

[0102] The method for preparing a lithium-sulfur battery using the modified lithium-sulfur battery diaphragm in this embodiment is the same as that in Example 1.

[0103] Example 6

[0104] A spinel oxide N of this embodiment i0.2 Fe 0.8 Co 2 O 4 The synthesis method comprises the following steps:

[0105] ((1) Weigh 1.280472 g (8 mmol) of anhydrous ferric nitrate, 0.3654 g (2 mmol) of anhydrous nickel nitrate and 5.8207 g (20 mmol) of cobalt nitrate hexahydrate into a planetary ball mill. The main disc speed is 120 r / min and the ball mill is performed for 30 min.

[0106] (2) Weigh 2.6325 g (45 mmol) of sodium chloride and 3.35475 g (45 mmol) of potassium chloride respectively and add them to the planetary ball mill described in step (1). The main disk speed is 120 r / min and the ball mill is performed for 30 min.

[0107] (3) Based on step (2), take out the ball-milled material and put it into a 50 mL quartz crucible.

[0108] (4) Based on step (3), the crucible is placed in a muffle furnace, kept at 450° C. for 2 h, naturally cooled, rinsed with deionized water and ethanol, and dried to obtain spinel oxide N i0.2 Fe 0.8 Co 2 O 4 .

[0109] A method for preparing a modified lithium-sulfur battery diaphragm of this embodiment comprises the following steps:

[0110] The spinel oxide N i0.2 Fe 0.8 Co 2 O 4 The mixture is uniformly mixed with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and coated on a polypropylene microporous membrane Celgard2400 separator, and the N-methylpyrrolidone (NMP) is volatilized to obtain a lithium-sulfur battery modified separator.

[0111] The method for preparing a lithium-sulfur battery using the modified lithium-sulfur battery diaphragm in this embodiment is the same as that in Example 1.

[0112] Example 7

[0113] A spinel oxide N of this embodiment i0.3 Fe 0.7 Co 2 O 4 The synthesis method comprises the following steps:

[0114] (1) Weigh 1.120413 g (7 mmol) of anhydrous ferric nitrate, 0.5481 g (3 mmol) of anhydrous nickel nitrate, and 5.8207 g (20 mmol) of cobalt nitrate hexahydrate into a planetary ball mill. The main disc speed is 90 r / min and the ball milling is carried out for 30 min.

[0115] (2) Weigh 2.6325 g (45 mmol) of sodium chloride and 3.35475 g (45 mmol) of potassium chloride respectively and add them to the planetary ball mill described in step (1). The main disk speed is 90 r / min and the ball mill is performed for 30 min.

[0116] (3) Based on step (2), take out the ball-milled material and put it into a 50 mL quartz crucible.

[0117] (4) Based on step (3), the crucible is placed in a muffle furnace, kept at 450° C. for 2 h, naturally cooled, rinsed with deionized water and ethanol, and dried to obtain spinel oxide N i0.3 Fe 0.7 Co 2 O 4 .

[0118] A method for preparing a modified lithium-sulfur battery diaphragm of this embodiment comprises the following steps:

[0119] The spinel oxide N i0.3 Fe 0.7 Co 2 O 4 The mixture is uniformly mixed with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and coated on a polypropylene microporous membrane Celgard2400 separator, and the N-methylpyrrolidone (NMP) is volatilized to obtain a lithium-sulfur battery modified separator.

[0120] The method for preparing a lithium-sulfur battery using the modified lithium-sulfur battery diaphragm in this embodiment is the same as that in Example 1.

[0121] Example 8

[0122] A spinel oxide CoFe in this embodiment 2 O 4 The synthesis method comprises the following steps:

[0123] (1) Weigh 1.82943 g (10 mmol) of anhydrous cobalt nitrate and 8.0799 g (20 mmol) of ferric nitrate nonahydrate into a planetary ball mill and mill at a main disc speed of 120 r / min for 30 min.

[0124] (2) Weigh 2.6325 g (45 mmol) of sodium chloride and 3.35475 g (45 mmol) of potassium chloride respectively and add them to the planetary ball mill described in step (1). The main disk speed is 120 r / min and the ball mill is performed for 30 min.

[0125] (3) Based on step (2), take out the ball-milled material and put it into a 50 mL quartz crucible.

[0126] (4) Based on step (3), the crucible is placed in a muffle furnace, kept at 450° C. for 2 h, naturally cooled, rinsed with deionized water and ethanol, and dried to obtain spinel oxide CoFe 2 O 4 .

[0127] A method for preparing a modified lithium-sulfur battery diaphragm of this embodiment comprises the following steps:

[0128] The spinel oxide CoFe 2 O 4 The mixture is uniformly mixed with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and coated on a polypropylene microporous membrane Celgard2400 separator, and the N-methylpyrrolidone (NMP) is volatilized to obtain a lithium-sulfur battery modified separator.

[0129] The method for preparing a lithium-sulfur battery using the modified lithium-sulfur battery diaphragm in this embodiment is the same as that in Example 1.

[0130] Example 9

[0131] A spinel oxide CoAl in this embodiment 2 O 4 The synthesis method comprises the following steps:

[0132] (1) Weigh 1.82943 g (10 mmol) of anhydrous cobalt nitrate and 7.5026 g (20 mmol) of aluminum nitrate nonahydrate respectively and add them into a planetary ball mill. The main disc speed is 120 r / min and the ball milling is carried out for 60 min.

[0133] (2) Weigh 2.6325 g (45 mmol) of sodium chloride and 3.35475 g (45 mmol) of potassium chloride respectively and add them to the planetary ball mill described in step (1). The main disk speed is 120 r / min and the ball milling is carried out for 60 min.

[0134] (3) Based on step (2), take out the ball-milled material and put it into a 50 mL quartz crucible.

[0135] (4) Based on step (3), the crucible is placed in a muffle furnace, kept at 450° C. for 2 h, naturally cooled, rinsed with deionized water and ethanol, and dried to obtain spinel oxide NiCo 2 O 4 .

[0136] A method for preparing a modified lithium-sulfur battery diaphragm of this embodiment comprises the following steps:

[0137] The spinel oxide CoAl 2 O 4 The mixture is uniformly mixed with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and coated on a polypropylene microporous membrane Celgard2400 separator, and the N-methylpyrrolidone (NMP) is volatilized to obtain a lithium-sulfur battery modified separator.

[0138] The method for preparing a lithium-sulfur battery using the modified lithium-sulfur battery diaphragm in this embodiment is the same as that in Example 1.

[0139] Example 10

[0140] A spinel oxide (NiCo)(FeAl)O 4 The synthesis method comprises the following steps:

[0141] (1) Weigh 0.9135 g (5 mmol) of anhydrous nickel nitrate, 0.914715 g (5 mmol) of anhydrous cobalt nitrate, 4.03995 g (10 mmol) of ferric nitrate nonahydrate, and 3.7513 g (10 mmol) of aluminum nitrate nonahydrate into a planetary ball mill. The main disc speed is 120 r / min and the ball milling is carried out for 60 min.

[0142] (2) Weigh 2.6325 g (45 mmol) of sodium chloride and 3.35475 g (45 mmol) of potassium chloride respectively and add them to the planetary ball mill described in step (1). The main disk speed is 120 r / min and the ball milling is carried out for 60 min.

[0143] (3) Based on step (2), take out the ball-milled material and put it into a 50 mL quartz crucible.

[0144] (4) Based on step (3), the crucible is placed in a muffle furnace, kept at 350° C. for 2 h, naturally cooled, rinsed with deionized water and ethanol, and dried to obtain spinel oxide (NiCo)(FeAl)O 4 .

[0145] A method for preparing a modified lithium-sulfur battery diaphragm of this embodiment comprises the following steps:

[0146] The spinel oxide (NiCo)(FeAl)O 4 The mixture is uniformly mixed with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and coated on a polypropylene microporous membrane Celgard2400 separator, and the N-methylpyrrolidone (NMP) is volatilized to obtain a lithium-sulfur battery modified separator.

[0147] The method for preparing a lithium-sulfur battery using the modified lithium-sulfur battery diaphragm in this embodiment is the same as that in Example 1.

[0148] See also Fig.10 , Fig.10The cyclic performance diagram of the spinel oxides prepared in Example 1, Example 2 and Example 3 for lithium-sulfur battery modified diaphragms shows that when the discharge capacity is similar, Example 1 (NiCo 2 O 4 ), Example 2 (FeCo 2 O 4 ) and Example 3 (Co 3 O 4 ) prepared by the present invention has a higher Coulombic efficiency (Coulombic Efficiency) than that of the ordinary film (PP), and the battery loses less charge during the charging and discharging process, and the battery efficiency is higher. It can be seen that the spinel oxide with precisely controlled sites in the present application can indeed enhance the conductivity and ion diffusion capacity of the material, improve the electrochemical performance of the material, and have great performance advantages in high-rate discharge and long-cycle applications.

[0149] A spinel oxide of the present invention achieves efficient and precise control of cations in the tetrahedral and octahedral positions in the spinel structure by means of a reasonable ratio of anhydrous metal nitrate and hydrated metal nitrate and by using molten salt as a reaction medium, so that the structure of the spinel oxide material is more stable, the chemical composition is uniform, and the chemical uniformity and phase purity of the material are improved; the spinel oxide with precisely controllable sites is applied to a modified diaphragm for a lithium-sulfur battery and a lithium-sulfur battery, which significantly improves the performance of the lithium-sulfur battery diaphragm, solves the problem that traditional diaphragm materials are prone to structural collapse or degradation after multiple charge and discharge cycles, and significantly prolongs the cycle life of the lithium-sulfur battery. The present invention has broader application prospects in the field of lithium-sulfur batteries.

[0150] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. A spinel oxide, characterized in that: It is synthesized from anhydrous metal nitrate and hydrated metal nitrate using molten salt as a reaction medium; its structural type is AB2O4 type, and its microstructure is a layered structure or a flower-like structure formed by the accumulation of nanosheets.

2. The spinel oxide according to claim 1, characterized in that: A and B can be mono-element or poly-element, A is one or more of Ni, Co, Fe, Mn, Cu, Zn and Mg, and B is one or more of Co, Fe, Al and Cr.

3. A method for synthesizing the spinel oxide according to any one of claims 1 to 2, comprising the following steps: Mixing anhydrous metal nitrate and hydrated metal nitrate in a corresponding ratio of 1 to obtain a mixed precursor material; Selecting a molten salt medium and the mixed precursor material in a corresponding ratio of 2, and heating them to obtain a spinel structure oxide; Wherein, the molar ratio of the corresponding ratio 1 is 1:1-3; the molar ratio of the corresponding ratio 2 is 1:1-5.

4. The method for synthesizing spinel oxide according to claim 3, characterized in that: The anhydrous nitrate metal salt is a mixture of one or more of the following: anhydrous nickel nitrate (Ni(NO3)2), anhydrous ferrous nitrate (Fe(NO3)2), anhydrous ferric nitrate (Fe(NO3)3), anhydrous cobalt nitrate (Co(NO3)2), anhydrous manganese nitrate (Mn(NO3)2), anhydrous copper nitrate (Cu(NO3)2), anhydrous zinc nitrate (Zn(NO3)2), and anhydrous magnesium nitrate (Mg(NO3)2).

5. The method for synthesizing spinel oxide according to claim 3, characterized in that: The hydrated metal nitrate salt is a mixture of one or more of the following: cobalt nitrate hexahydrate (Co(NO3)2·6H2O), iron nitrate nonahydrate (Fe(NO3)3·9H2O), chromium nitrate nonahydrate (Cr(NO3)3·9H2O), and aluminum nitrate nonahydrate (Al(NO3)3·9H2O).

6. The method for synthesizing spinel oxide according to claim 3, characterized in that: The molten salt medium is a mixture of one or more of the following: potassium chloride (KCl), sodium chloride (NaCl), sodium nitrate (NaNO3), potassium nitrate (KNO3), calcium chloride (CaCl2), magnesium chloride (MgCl2), sodium carbonate (Na2CO3), and sodium sulfate (Na2SO4).

7. The method for synthesizing spinel oxide according to claim 3, characterized in that: The mixing method is a planetary ball mill, the main disc speed is 50-450r / min, the grinding jar speed is 100-900r / min, the ball milling time is 0-2h; the heating temperature is 300-800°C, and the time is 1-12h.

8. A modified diaphragm for a lithium-sulfur battery, characterized in that: It comprises the spinel oxide according to any one of claims 1 to 2.

9. A method for preparing a modified diaphragm for a lithium-sulfur battery, characterized in that: The following steps are involved: The spinel oxide according to any one of claims 1 to 2 is uniformly mixed with polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP), and coated on a diaphragm, and the N-methylpyrrolidone (NMP) is volatilized to obtain the modified diaphragm for a lithium-sulfur battery.

10. A lithium-sulfur battery, comprising the lithium-sulfur battery modified separator according to claim 9.